Folk, Rituals and Political Change: A Contextual Reading of Bruised Evening - Rijal, Shiva (Literary Studies, 2023)
One of the major characteristics of politic al and social change is the shift that takes place in the perceptions about polity and identity of people. During such shifting times, writers and artists dare to articulate public aspirations through aesthetic expressions of new order. Like political leaders and social activities, creative writers and artists too own up the responsibility of talking about the presentism by taking a stand about the methodology of looking at the history of both the nation as well as of the modes of expression. Evoking such shifting nature of aesthetic forms and expressions, the famous twentieth century English theatre and culture critic Raymond Williams writes: